Efficacy analysis of prophylactic hyperthermic intraperitoneal chemotherapy in patients with locally advanced gastric cancer: a retrospective study - Zhijie Gong; Zhijie Gong; Liping Zhou; Yinghao He; Yinghao He; Jun Zhou; Yanjie Deng; Zudong Huang; WeiWei Wang; Qiangbang Yang; Jian Pan; Yingze Li; et al. (Frontiers in Oncology)
PurposeThis study aims to evaluate the effectiveness and safety of prophylactic hyperthermic intraperitoneal chemotherapy (P-HIPEC) in patients with locally advanced gastric cancer (AGC) after laparoscopic radical gastrectomy. Additionally, it explores how the frequency and timing of P-HIPEC influence treatment outcomes.MethodsA retrospective analysis was conducted on 227 patients with locally AGC who underwent laparoscopic surgery at Maoming People’s Hospital from January 2016 to December 2022. Patients were stratified into the HIPEC group (n=101) and the non-HIPEC group (n=126), based on whether they received postoperative P-HIPEC. Propensity score matching (PSM) was used to adjust for baseline characteristics, facilitating a comparative analysis of survival outcomes, postoperative complications and recurrence patterns. Cox regression analysis was performed to identify prognostic factors. Furthermore, the impact of varying P-HIPEC frequencies and initiation timings was evaluated.ResultsNo significant differences in overall survival (OS) or postoperative complication rates were observed between the two groups in the original and PSM cohorts. But the disease-free survival (DFS) of the HIPEC group was significantly higher than that of the non-HIPEC group (HR 0.569; 95% CI 0.362–0.894; p = 0.013) in the PSM cohort, with 1-year, 3-year, and 5-year DFS rates showing notable improvement (77.9% vs. 69.7%, 60.1% vs. 43.0%, and 46.2% vs. 25.5%). The incidence of isolated peritoneal metastasis (PM) was significantly lower in the HIPEC group (5.3% vs. 17.3%, p = 0.039). Multivariate Cox regression analysis identified P-HIPEC as an independent protective factor for DFS. Further analysis indicated that neither the number of P-HIPEC sessions had a significant impact on OS (p = 0.388) or DFS (p = 0.735), nor did the timing of P-HIPEC initiation affect OS (p = 0.620) or DFS (p = 0.488). Likewise, different P-HIPEC frequencies or initiation timings had no significant impact on postoperative complication rates or recurrence patterns.ConclusionP-HIPEC effectively reduces the risk of postoperative PM and improves DFS in patients with locally AGC without increasing postoperative complications. However, it does not significantly impact OS. Additionally, variations in the frequency and timing of P-HIPEC initiation do not significantly affect survival outcomes, postoperative complications, or recurrence patterns.